Fonctions de la recherche et participation : une épistémo-compatibilité dans le cas de la recherche-intervention - Jean-François Marcel (Université de Provence, 2020)
This article examines the connection between the heuristic and critical functions of educational research and the praxeological function, more specifically, in the case of a participatory approach. The examination of the conditions of the mobilization of the three functions in the context of participation allows us to analyze their "epistemo-compatibility". The argument is based on the case of the research-intervention approach, an approach based on the articulation of inseparable heuristic, critical and praxeological aims. These three aims are anchored in the primary principle of participation.A two-step analysis is used to examine the epistemic compatibility of participation with each of the three functions of educational research. The first stage approaches participation from the three functions, while the second stage approaches the aims from the three circles that correspond to the levels of participation at work in intervention research.